BEHIND THE MULTICULTURAL IMAGE OF THE CRUISE TOURISM - Putu Titah Kawitri Resen (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
Cruise tourism is a type of travel that involves taking advantage of all of the activities and facilities available on a cruise ship. In cruise tourism, the ship is not only a mode of transportation but a tourist destination itself. The diverse nationalities of the workforce aboard cruise ships set it apart from other tourism industries. As a result, the cruise industry has promoted multiculturalism in a favorable light. This article aims to explain how the positive image of multinational workers does not prevent companies from having an expansive and exploitative character, as suspected by the radical political economy perspective. This study refers to this perspective to analyze the nature of a cruise ship company behind the multicultural image it offers. This study concludes that multinational workers who are used to form a positive image of the company are produced through a labor flexibility strategy that can reduce operational costs and bring maximum profits to company owners.Keywords: cruise tourism, image, multicultural